Empowering communities to manage natural resources: where does the new power lie?: a case study of Duru-Haitemba, Babati, Tanzania - Kajembe, G.C.; Monela, G.C. (2000)
Recent approaches to community-based natural resource management appear as diverse as their varied implementing agencies and natural resource settings; yet they rest on a set of common assumptions about community, natural resources and the relationship between them. This paper focuses on power relations between local actors and how these set the framework for resource management in Duru-Haitemba. As one of the few remaining tracts of Miombo woodlands, the Duru-Haitemba had been targeted for gazzettment. However the exercise faced ‘local discontent’, originating in the ‘generalized narrative’. Before colonial powers the community lived in balanced harmony with nature, which when disrupted led to disequilibrium and hence degradation. A range of factors may account for this, including: technological change; breakdown of traditional authority; social change; urban aspirations and intrusion of inappropriate state policies. The community and environment should be brought back into harmony. This requires either the discovery and rebuilding of traditional collective resource management institutions or their replacement by new ones. At the local level the elites and the traditionalists compete for power: The primary concern of traditionalists is ‘ritual’. Elites tend to hijack community-based processes and forcefully occupy the political space opened by decentralisation. Besides power struggles at the micro level, another challenge is the government leadership at the macro level. Government officials usually have very mixed feelings about community actions but increasingly are realising that community action can be substituted for the expensive exercise of putting government officials in the field. The paper points out that community-based natural resource management is a plausible way to reduce public costs of managing resources. However, the power struggle between local communities, field agents and supervisors remains. This ‘triangle’ of relationships constitutes the social arena marking out the actual ‘locale’ of community based natural resource management in Duru-Haitemba.